Children’s Innate Capacity of Learning the First Language: an Overview of Structure-dependent Rules - Achmad Farid; Foad Elbakai; Achmad Fanani (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
How children acquire their first language has always been a question of debate between generativists and cognitive functionalists. Crain and Nakayama (1987) attempt to support the notion that children are innately equipped with syntactic rules and such rules are not learned by the child. They want to persuade functionalist linguists with the rightness of the innateness of the structure-dependent hypothesis (i.e. Universal Grammar/UG and poverty of the stimulus notion). To be precise, Crain and Nakayama discuss the Chomskyain “movement transformation” hypothesis (.i.e. subject/aux inversion in structures with relative clauses). They claim that children do not make errors when attempting to make polar interrogatives from relative clauses; as a result, they reserve the verb inside the relative clause and move the auxiliary in the main clause to the front. For example, children would not form structures like *Is the author who writing this task is confused? This is attributable to the claim that children are innately wired with structure-dependent rule. That is to say, children resort to what so-called innate schematism (UG principles) when they form yes/no questions. This assertion is based on nothing more than the claim that no structure-dependence errors were found so far in the child’s speech. Also, they conclude that grammar and meaning are disconnected from “the autonomy of syntax”. To support their view, Crain and Nakayama conducted a study on thirty children whose age ranged from three to five. This paper is primarily intended to critically review Crain and Nakayama’s article and discuss the structure-dependence rule in favour of both a formalist and cognitive functionalist point of view.